The effects of adjuvant endocrine therapy on long-term outcomes from ductal carcinoma in situ: a systematic review and meta-analysis - Qian Chen; Ian Campbell; Mark Elwood; Alana Cavadino; Phyu Sin Aye; Sandar Tin Tin (Breast)
Background: Although adjuvant endocrine therapy (ET) is a standard treatment for hormone receptor positive ductal carcinoma in situ (DCIS), its use is variably recommended by clinicians. This paper reviewed the effects of ET in relation to recurrence and survival across diverse populations. Methods: PubMed, Embase, Web of Science, and Cochrane were searched for studies that reported outcomes of DCIS treated with ET versus no ET. Results: Three randomised trials and 42 cohort studies were included. In the trials, tamoxifen significantly reduced the risk of in-breast recurrence with a pooled hazard ratio (HR) of 0.69 (95 % CI: 0.60, 0.80). In the cohort studies, ET was associated with lower risks of any recurrence (HR 0.67; 95 % CI: 0.55, 0.83), ipsilateral breast tumour recurrence (HR 0.59; 0.51, 0.69), loco-regional recurrence (HR 0.74; 0.53, 1.02) and contralateral breast cancer (HR 0.70; 0.49, 1.00), and improved overall survival (HR 0.85; 0.79, 0.90). No significant association between ET and breast cancer specific survival was observed in either trials or cohort studies. Subgroup analyses within the cohort studies showed no significant differences in the pooled HRs for recurrence and survival by follow-up length, confounding adjustment or treatment type. Conclusions: The use of adjuvant ET reduces the risk of recurrence in patients with DCIS in clinical trials, as well as in the real-world setting. Survival benefits, however, warrant further study.